The preoperative and postoperative experiences of mastectomy patients with and without neoadjuvant therapy - Esteban, Marcus Juan L.; Bautista, Fraingeli Camille D.; de Lemos, Marian Angelica V.; Dumlao, Lenore Anne D.; Fabregar, Anton Carlo O.; Lisondra, Lady Nancy C.; Montalbo, Maricor C.; Ortega, Giselle A.; Rigunay, Maria Carmela T.; Toribio, Dianne M.; Untalasco, Zyena Joyce P.; Valdez, Aileen Mae C.
This research aimed to describe the perioperative experiences between patients who underwent mastectomy with neoadjuvant therapy and those without neoadjuvant therapy in terms of anxiety levels and post-operative wound conditions.